Personal Determinants of Emotional Burnout in Students (Future Physical Training Teachers) - Koltunovych, Tetiana; Oliinyk, Maria; Perepeliuk, Inna; Kvasetska, Yaryna (LUMEN Publishing House, 2021)
Purpose: The purpose of the study is to identify and analyze the manifestations of emotional burnout of future physical education teachers and to determine the role of personal determinants in the formation and overcoming this condition. The purpose was specified in the following tasks: to identify the features of emotional burnout in future physical training teachers; to investigate the relationships between emotional burnout and personal characteristics of students; to find out the differences in the sets of personality characteristics of students of future physical training teachers with different levels of emotional burnout. Design and Methods: The research involved 150 students of the college (18.1±2 years) who study in the specialty “physical training and sports”: the 1st year, n=50; 2nd year, n=32; 3rd year, n=37 and 4th year, n=31). The sample is heterogeneous (61.33% of boys, 38.67% of girls). The Maslach Burnout Inventory (C. Maslach), “Diagnostics of the level of emotional burnout” (V.V. Bojko), the modified form of the FRI questionnaire was employed. Methods of descriptive statistics, Spearman correlation analysis, Kruskal-Wallis one-way analysis of variance and structural analysis (by A.V. Karpov) were used. Mathematical data processing and graphical presentation of the results were carried out using the computer software package of statistical software SPSS 22.0. Results: The article confirms the assumption about the existence of correlation relations between emotional burnout and personal characteristics of future physical training teachers. The statistically significant differences between groups of students with different levels of emotional burnout on the scale of “neuroticism”, “spontaneous aggression”, “depression”, “emotional lability”, “irritability”, “reactive aggression”, “openness” that are more common to future teachers with high level of emotional burnout are revealed. It is empirically proven that students with different levels of emotional burnout characterized by various structural organizations of personality characteristics, and also that the growth of indicators of the emotional burnout formation is accompanied by a qualitative restructuring of the personality characteristics. Conclusions: The obtained data contributes to the study of the phenomenon of burnout and provide an opportunity to identify further directions of its prevention and correction among future physical training teachers. Subsequent studies will be aimed at developing an individual system of psychological training and support for the prevention and correction of emotional burnout among students.
Koltunovych, T., Oliinyk, M., Perepeliuk, I., & Kvasetska, Y. (2021). Personal Determinants of Emotional Burnout in Students (Future Physical Training Teachers). In O. Clipa (vol. Ed.), Lumen Proceedings: Vol. 16. ATEE 2020 - Winter Conference. Teacher Education for Promoting Well-Being in School. (Suceava, 2020). Iasi, Romania: LUMEN Publishing House, 2021. P. 191–210. URL: https://doi.org/10.18662/lumproc/atee2020/14
Keywords: future physical training teachers; exhaustion; depersonalization; personality characteristics of an individual; reduction of personality achievements; emotional burnout